Swedish Student Humour in the 1720s: Johan Risell's Satire on the Town Åmål - Burman, Lars (Nordlit, 2023)
Johan Risell (1697-1724) is almost unknown today, but acknowledged in his time for his vivid imagination and ability to convey emotions. He died just after the Great Northern War. His works were scattered, and less than ten poems were known. The present article is a step in reclaiming Risell’s place in Swedish literary history. ”Staden Åmåls och des Inbyggares Beskrifning” (”A depiction of the town Åmål and its inhabitants”)  is one of the poems which were known,  though it was not printed until 1873. The article shows that the satire was circulated in manuscript to expectant readers during the 18th century. Since it was considered to be a disreputable pasquil, not least by the citizens of the little countryside town Åmål, it was held back from the public. The aesthetically refined literary critics of the early 19th century considered it to lack in taste, and were unable to see its qualities. In the article the Åmål poem is studied from literary, biographical and sociological perspectives. Its relation to the genre “encomium urbis”,  and to the literary town praises of Sweden’s “Era of Greatness”, is described. Risell died young, and it is maintained that his satirical poem is to be understood against a backdrop of early student culture. Risell’s poem is given a fuller context since the article’s author can draw on a hitherto unknown manuscript containing more then 50 new poems by Risell.
Keywords: poetry; satire; student culture; 18th century; Johan Risell; Åmål